Peningkatan Kemampuan Berhitung Melalui Metode Bermain Kereta Angka Pada Anak Kelompok A di TK Tunas Harapan - Yesi Lestari; Nurmalina Nurmalina; Musnar Indra (Jurnal Pendidikan Tuntas, 2023)
This research aims to assess the effectiveness of the number train play method in enhancing counting skills in group A children. Counting skills are fundamental cognitive abilities essential in a child's developmental process. This study involved 12 children aged 4-5 years who were enrolled in a local kindergarten's group A.The research was conducted using a quantitative approach with a quasi-experimental design. Participants were divided into two groups: the experimental group, receiving instruction through the number train play method, and the control group, receiving conventional instruction. Data were collected through pre-test and post-test assessments measuring the children's counting abilities.The research results show that the group receiving instruction through the number train play method experienced a significant improvement in their counting skills, while the control group exhibited a lower level of improvement. Data analysis using a t-test revealed a significant difference between the two groups at a significance level of 0.05.This research concludes that the number train play method is effective in enhancing counting skills in group A children. The implications of this study are that play-based methods can be a valuable choice for early childhood counting instruction, offering a more enjoyable and interactive learning experience. It is expected that this research can contribute to the development of more effective teaching methods for early childhood education. Keywords: Cognitive abilities, recognizing number symbols, method of playing number trains.